2006
DOI: 10.1007/s10484-006-9009-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Resonance in Heart Rate Variability Stimulated by Biofeedback

Abstract: As we previously reported, resonant frequency heart rate variability biofeedback increases baroreflex gain and peak expiratory flow in healthy individuals and has positive effects in treatment of asthma patients. Biofeedback readily produces large oscillations in heart rate, blood pressure, vascular tone, and pulse amplitude via paced breathing at the specific natural resonant frequency of the cardiovascular system for each individual. This paper describes how resonance properties of the cardiovascular system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
290
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(329 citation statements)
references
References 27 publications
(29 reference statements)
5
290
2
5
Order By: Relevance
“…We found that even when the breathing frequency is higher than 0.15 Hz, the RSA and the LF oscillations may coincide, but do not produce a resonant effect, note the presence of VLF oscillations (Figure 4). Further discussion on this point can be found in: Vaschillo et al (2006), Cysarz et al (2005), Peng et al (1999). For the Zen Master (Figure 5), the same pattern as shown for ZI is observed, with two different phases in the meditation; however, for ZM, even in the second half, the breathing oscillates exclusively in the LF range and the resonant effect never disappears.…”
Section: Crisis Zonesupporting
confidence: 61%
“…We found that even when the breathing frequency is higher than 0.15 Hz, the RSA and the LF oscillations may coincide, but do not produce a resonant effect, note the presence of VLF oscillations (Figure 4). Further discussion on this point can be found in: Vaschillo et al (2006), Cysarz et al (2005), Peng et al (1999). For the Zen Master (Figure 5), the same pattern as shown for ZI is observed, with two different phases in the meditation; however, for ZM, even in the second half, the breathing oscillates exclusively in the LF range and the resonant effect never disappears.…”
Section: Crisis Zonesupporting
confidence: 61%
“…Each session included four five-minute periods of resonant breathing with two mi-nutes of rest after each period. In order to maximize HRV during the training sessions, small adjustments in individual breathing frequency were made, as previously described (Vaschillo et al 2006). Subjects received visual HRV feedback during resonance frequency breathing.…”
Section: Resonance Hrv Biofeedbackmentioning
confidence: 99%
“…Antagonistic modulation of the heart via the parasympathetic and sympathetic branches of the ANS is reflected by fast and slow oscillations in beat-to-beat heart rate (Berntson et al 1997). One way to increase HRV is through slow paced breathing using HRV biofeedback (BF) (Vaschillo et al 2006). The amplitude of HRV is maximized during slow breathing, approximately six breaths per minute.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the HeartMath intervention employs heart rhythm coherence biofeedback in conjunction with positive emotion-focused self-regulation techniques to activate the coherence mode, heart rhythm coherence can also be achieved using other HRV biofeedback protocols, such as those reported by Lehrer and colleagues, who use the term ''resonance'' to describe the target physiological state (Lehrer et al 2000;Vaschillo et al 2006). HRV biofeedback has been shown to increase HRV and heart rhythm coherence and to produce positive outcomes in various populations, including clinically significant improvements in asthma (Lehrer et al 2004), hypertension (McCraty et al 2003), and depression (Karavidas 2008;Siepmann et al 2008).…”
Section: Description Of Intervention Programmentioning
confidence: 99%